CuO-GO-Ag; Green Synthesis With Fagonia Arabica and Biomedical Potential is a Bioinspired Nano Theranostics Composite - Shahid, Sammia; Mansoor, Sana; Javed, Mohsin; Iqbal, Shahid; Yousaf, Umair; Alsaab, Hashem O.; Awwad, Nasser S.; Ibrahium, Hala A.; Alzhrani, Rami M.; Alqahtani, Mashael D.; Tamam, Nissren; Elkaeed, Eslam B.; et al. (Frontiers in Materials, 2022)
Using biological components from Fagonia arabica, we were able to synthesise CuO-GO-Ag nanocomposites (NCs). The antioxidant and anti-inflammatory activities of the NCs that were produced were also tested. SEM, XRD, UV-Vis, and EDX were used to analyze CuO-GO-Ag NCs. The hydrothermal and hummer methods were used to make graphene oxide (GO). To assess the efficacy of our manufactured composite, UV-vis spectroscopy was utilized to examine anti-inflammatory activity and antioxidant efficiency of CuO-GO-Ag nanocomposite. Results reveal that biologically synthesized CuO-GO-Ag NCs have high scavenging and inflammation reduction potential as compared to standards (ascorbic acid, diclofenac sodium). CuO-GO-Ag showed that scavenging efficiency for 0.3mg/ml is 57.40% and for 0.5mg/ml is 74.24% while scavenging efficiency for standard (ascorbic acid) is 44.22 % for 0.3mg/ml and 58.42% for 0.5mg/ml. Likewise, CuO-GO-Ag nanocomposite showed a % inhibition value of 46.59 and 87.80 at 0.1mg/ml and 0.5mg/ml while diclofenac sodium showed a % inhibition value of 10.98 and 35.37 a similar concentration. Fagonia arabica seems to be a good source for acclimating the potential of NCs and nanoparticles toward different increased biological activities, according to the findings.